Creation and Implementation of an EMS Elective for Final-Year Medical Students: A 5-year Evaluation - Edder Peralta; Christopher Evers; Toniann Gonell; Megan Hodges; David Cohen; Lauren M. Maloney (Western Journal of Emergency Medicine, 2025)
Introduction: Emergency medical services (EMS) professionals interact with nearly every type of physician and are key stakeholders across the healthcare spectrum. However, no formal national recommendations exist for medical student education about EMS. When looking for institution-level resources to assist in writing the educational objectives and curricular content for an EMS elective for medical students, limited examples are available for guidance. We designed, implemented, and evaluated a two-week EMS elective for final-year medical students. A pragmatic description of how to create an EMS elective is detailed. Methods: The EMS elective involves an introductory session, an operational orientation, and six ambulance shifts. Self-directed activities and checklists encourage interdisciplinary learning between calls. Additionally, students deliver a case presentation including an example for improved interdisciplinary communication. Before and after the elective, a voluntary anonymous survey is distributed, in addition to a formal standard course evaluation. Results: From 2017–2022, 37 students participated in the elective. Thirty-four (92%) submitted the pre-elective survey, and 21 (57%) submitted the post-elective survey. Mann-Whitney U testing suggested an improved understanding of the capabilities of different EMS practitioner levels and of the different types of medical oversight after the elective (median pre=60%, median post=90%, U=118, P<0.001). Qualitatively, students described their experiences as “practical,” “hands-on,” and “eye-opening.” Conclusion: An EMS elective using andragogy and intentional interdisciplinary communication seems useful in facilitating improved understanding of the fundamentals of EMS practice for final-year medical students.